2006
DOI: 10.1097/01.ccm.0000206288.90613.1c
|View full text |Cite
|
Sign up to set email alerts
|

Power of breathing determined noninvasively with use of an artificial neural network in patients with respiratory failure*

Abstract: POB can be calculated noninvasively with reasonable clinical accuracy for patients receiving ventilatory support by using an ANN. This method obviates the need for inserting an esophageal catheter and thus greatly simplifies measurement of POB. POB(N) may be a clinically useful tool for consideration when setting PSV to unload the respiratory muscles. Before considering its use in clinical practice, POB(N) would need to be incorporated within the context of load tolerance and shown to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Although they cannot deal with missing data, ANNs can simultaneously handle numerous variables by building models with reference to outliers and nonlinear interactions among variables. [4][5][6] Whereas conventional statistical methods reveal parameters that are significant only for the overall population, ANNs include parameters that are significant at the individual level even if they are not significant for the overall population. Unlike other standard statistical tests, ANNs can also manage complexity even when the sample size is small and even when the ratio between variables and records is unbalanced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although they cannot deal with missing data, ANNs can simultaneously handle numerous variables by building models with reference to outliers and nonlinear interactions among variables. [4][5][6] Whereas conventional statistical methods reveal parameters that are significant only for the overall population, ANNs include parameters that are significant at the individual level even if they are not significant for the overall population. Unlike other standard statistical tests, ANNs can also manage complexity even when the sample size is small and even when the ratio between variables and records is unbalanced.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other standard statistical tests, ANNs can also manage complexity even when the sample size is small and even when the ratio between variables and records is unbalanced. [4][5][6] That is, ANNs avoid the dimensionality problem. The large and homogeneous data set in this study enabled robust network training because all clinical variables had shown potential effects on mortality in previous logistic regression models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An artificial neural network can be used to estimate power of breathing noninvasively, without the need for an esophageal catheter in patients with respiratory failure. 42 In one study, a WOB/min of Ͻ 10 J/min was predictive of subjects' ability to be liberated from mechanical ventilation. 43 Adaptive support ventilation (ASV) is based on the concept of minimum WOB, which suggests that the patient will breathe at a V T and breathing frequency that minimize the elastic and resistive loads while maintaining oxygen- Fig.…”
Section: Work Of Breathingmentioning
confidence: 99%
“…WOB is calculated from the measured V I and the P calculated from the equation of motion: WOB ϭ ͐P ϫ V. Power of breathing (WOB/min) is the rate at which work is done as a measure over time, not for an individual breath. [42][43][44][45][46] This may be a better assessment of respiratory muscle load than WOB/breath. Normal power of breathing is 4 -8 J/min.…”
Section: Work Of Breathingmentioning
confidence: 99%